Observation of parametric X-rays produced by 400 GeV/c protons in bent crystals; Physics Letters B; Vol. 701, iss. 2 - Scandale W.; Arduini G.; Assmann R.; Cerutti F.; Gilardoni S.; Uglov S. R. Sergey Romanovich; Gogolev A. S. Aleksey Sergeevich (2011, 2011)
Title screen